IMPROVE YOUR ENGLISH THROUGH SONGS (Modern education and development, 2025)
The use of music as a pedagogical tool in language learning has gained considerable attention in applied linguistics and educational psychology. This paper explores how songs can improve English language acquisition, focusing on vocabulary development, pronunciation, listening comprehension, and cultural literacy. Through a review of empirical studies, this article demonstrates the effectiveness of music as a multimodal learning aid that stimulates cognitive and affective processes involved in second language acquisition (SLA).